Propuesta de reestructuración de la gestión empresarial para Laptrom Cía. Ltda. - Reina Abata, Erika Janina (2013)
This proposal is the result of a methodical process seated in the existing theory and the information provided by the company under study. LAPTROM is a company dedicated to the marketing of computer equipment in order to meet the needs of consumers.